Labor Market Transitions in Egypt Post-Arab Spring - Deng, Jingyuan (World Bank, Washington, DC, 2022)
This paper examines the Arab Republic of Egypt’s labor market transition dynamics post–Arab Spring based on the two most recent rounds of the Egypt Labor Market Panel Survey conducted in 2012 and 2018. In addition to providing disaggregated-level analysis by examining labor market transitions by gender, education, and age groups, the paper provides a cross-country, cross-regional perspective by comparing Egypt’s labor market transitions with Mexico’s, relying on data from the Encuesta Nacional de Ocupación y Empleo. To match the span of Mexico’s transitions (which are measured over a one-year period) and Egypt’s (which are measured over six years), the analysis uses Monte Carlo simulations of repeated discrete-time Markov chains. Based on these results, the Egyptian labor market appears to be highly rigid compared to the Mexican labor market, which instead shows a large degree of dynamism regardless of individual initial labor market states at baseline. Auxiliary regression analyses focusing on transitions to and from the dominant absorbing labor market states in Egypt —public sector employment for both genders, nonparticipation for women, and the informal sector for men—show that having a post-secondary education is associated with a lower probability of remaining out of the labor force for women who were already out of the labor force at baseline, while being married at baseline is found to be a significant predictor for women to stay out of the labor force if they were already so. Among men, the better educated are found to be more likely to secure formal employment, be it in the public or private sector, and are more likely to keep their public formal jobs once they secure them.